Novel Protein Biomarkers of Monoamine Metabolism Defects Correlate with Disease Severity - Tristán‐Noguero, Alba; Borràs, Eva; Molero‐Luis, Marta; Wassenberg, Tessa; Peters, Tessa; Verbeek, Marcel M.; Willemsen, Michel; Opladen, Thomas; Jeltsch, Kathrin; Pons, Roser; Thony, Beat; Horvath, Gabriella; et al. (Movement disorders, 2021)
ABSTRACT Background Genetic defects of monoamine neurotransmitters are rare neurological diseases amenable to treatment with variable response. They are major causes of early parkinsonism and other spectrum of movement disorders including dopa‐responsive dystonia. Objectives The objective of this study was to conduct proteomic studies in cerebrospinal fluid (CSF) samples of patients with monoamine defects to detect biomarkers involved in pathophysiology, clinical phenotypes, and treatment response. Methods A total of 90 patients from diverse centers of the International Working Group on Neurotransmitter Related Disorders were included in the study (37 untreated before CSF collection, 48 treated and 5 unknown at the collection time). Clinical and molecular metadata were related to the protein abundances in the CSF. Results Concentrations of 4 proteins were significantly altered, detected by mass spectrometry, and confirmed by immunoassays. First, decreased levels of apolipoprotein D were found in severe cases of aromatic L‐amino acid decarboxylase deficiency. Second, low levels of apolipoprotein H were observed in patients with the severe phenotype of tyrosine hydroxylase deficiency, whereas increased concentrations of oligodendrocyte myelin glycoprotein were found in the same subset of patients with tyrosine hydroxylase deficiency. Third, decreased levels of collagen6A3 were observed in treated patients with tetrahydrobiopterin deficiency. Conclusion This study with the largest cohort of patients with monoamine defects studied so far reports the proteomic characterization of CSF and identifies 4 novel biomarkers that bring new insights into the consequences of early dopaminergic deprivation in the developing brain. They open new possibilities to understand their role in the pathophysiology of these disorders, and they may serve as potential predictors of disease severity and therapies. © 2020 International Parkinson and Movement Disorder Society